Labour content of international trade in intermediates : the case of Portugal - Martínez-Galán, Enrique (2022)
This paper addresses the job content with regards to Portugal’s participation in the international fragmentation of production. Labour is considered both at the overall level and also by skills (high-skill, medium-skill, and low-skill). The assessment makes use of the World Input Output Database complemented by the Socio Economic Accounts for labour skill-types. The period analysed is the longest possible, bearing in mind the information available in the data bases used. The amount of labour (jobs) required to produce imported intermediates (exported intermediates) is taken as a proxy for the job effect of downward (upward) participation of the country in Global Value Chains. On one hand, we conclude that exports of intermediates were mostly intensive in the use of low-skilled labour, despite the skill upgrading observed over the period analysed. On the other hand, imports of intermediates were proportionally more intensive in the use of skilled labour, predominantly at the medium skill level, which is an expected result from a country where low-skilled labour is abundant. We also concluded that the estimated net job content embodied in the international trade of intermediates at the end of the period under analysis was, globally, negative to the amount of 51,000 jobs. Regional impacts arising from sectoral gains or losses in the job content of ex ported intermediates do not appear to have been relevant. .